Serum OPG/TRAIL ratio predicts the presence of cardiovascular disease in people with type 2 diabetes mellitus. (July 2022) - Forde, H.; Davenport, C.; Rochfort, K.D.; Wallace, R.G.; Durkan, E.; Agha, A.; Thompson, C.J.; Tormey, W.T.; O'Gorman, D.J.; Cummins, P.M.; Smith, D.
Abstract: Aims: Cardiovascular disease (CVD) is the leading cause of mortality in type 2 diabetes mellitus (T2DM). Epidemiological studies suggest serum Osteoprotegrin (OPG)/Tumour-necrosis-factor-related-apoptosis-inducing- ligand (TRAIL) ratio may be a useful marker of cardiovascular risk. This study aimed to compare serum levels of TRAIL, OPG and OPG/TRAIL ratio in people with T2DM, with and without a history of CVD, and controls; and to determine which of these indices, if any, predict cardiovascular risk. Methods: In this single centre observational study of 133 participants, people with T2DM, with and without a history of a cardiovascular event in the last 5 years, were recruited along with a control cohort without T2DM or CVD. Demographic information and anthropometric measurements were recorded. Blood samples were taken and OPG and TRAIL were measured using ELISA. Results: People with T2DM and CVD had higher OPG/TRAIL ratios compared to controls or those with a new diagnosis of T2DM. After adjustment for potential confounding factors, OPG/TRAIL ratio was significantly associated with the presence of CVD in people with T2DM and an OPG/TRAIL ratio cut-off > 38.6 predicted the presence of CVD in this cohort with a sensitivity of 80% and specificity of 82%. Conclusion: This study suggests that OPG/TRAIL ratio may have a role as a biomarker of CVD in people with T2DM.